Dream B - Kintanar, TG; VStudios ([S.l.] : VStudios, 2008)
TG Kintanar gives us remarkably insightful look at the beauty of finding the bigger picture and how finding your own'big piture' can make all difference. He tells us about Dream B, the dream that you are willing to risk everything for and how changing your outlook, your attitude and your vision can help you achieve it
Title from title screen
DVD format
Keywords: Dreams; Dream interpretation; Multilevel marketing; Direct marketing